Latis: A Spatial Decision Support System to Assess Low-Impact Site Development Strategies - G. Wayne Wilkerson; William H. McAnally; James L. Martin; Jeff A. Ballweber; Kim Collins Pevey; Jairo Diaz-Ramirez; Austin Moore (Advances in Civil Engineering)
Significant advances have been made in the use of spatial and hydrologic models to quantify the impact of Best Management Practices (BMPs) and Low-Impact Development (LID) practices on water quality. Further advances are the goal of this work to add selection of BMP/LID and calculation of implementation costs, all integrated into a spatial decision support system (DSS). The Hydrologic Simulation Program in FORTRAN (HSPF), an unsteady flow model, was combined with links to desktop spatial data analysis tools, a spreadsheet listing BMP/LID and their implementation, operation, and maintenance cost data. Testing of the DSS, named Latis, allowed improvements in direct design of BMP, and a survey of landscape and engineering practitioners provided the impetus for a simplified version, Latis-LIDIA.